International Symposium for Intelligent Transportation and Smart City (ITASC) 2019 Proceedings Branch of ISADS (The International Symposium on Autonomous Decentralized Systems) - Zeng, Xiaoqing; Xie, Xiongyao; Sun, Jian.; Ma, Limin; Chen, Yinong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents research advances in intelligent transportation and smart cities in detail, mainly focusing on green traffic and urban utility tunnels, presented at the 4th International Symposium for Intelligent Transportation and Smart City (ITASC) held at Tongji University, Shanghai, on May 8-10, 2019. It discusses a number of hot topics, such as the 2BMW system (Bus, Bike, Metro and Walking), transportation safety and environmental protection, urban utility design and application, as well as the application of BIM (Building Information Modeling) in city design. By connecting the theory and applications of intelligent transportation in smart cities, it enhances traffic efficiency and quality. The book gathers numerous selected papers and lectures, including contributions from respected scholars and the latest engineering advances, to provide guidance to researchers in the field of transportation and urban planning at universities and in related industries. The first conference in the ITASC series was held in 2013 as a workshop of the International Symposium on Autonomous Decentralized System (ISADS) in Mexico City. The second and third were held in May 2015 and May 2017, respectively, in Tongji University, Shanghai.
Green Transportation -- Urban Utility Tunnel -- Intelligent Traffic System -- Urban Planning.
Keywords: Transportation engineering; Traffic engineering; Geotechnical engineering; Sustainability; Telecommunication; Transportation Technology and Traffic Engineering; Geotechnical Engineering and Applied Earth Sciences; Sustainability; Communications Engineering, Networks